2015
DOI: 10.1159/000441501
|View full text |Cite
|
Sign up to set email alerts
|

Silencing Matrix Metalloproteinases 9 and 2 Inhibits Human Retinal Microvascular Endothelial Cell Invasion and Migration

Abstract: Purpose: Proliferative retinal angiogenesis may severely impair the retina. Previous studies have indicated that matrix metalloproteinase (MMP)-2 and MMP-9 play important roles in the process of retinal angiogenesis. In this study, we suppressed MMP-2 and MMP-9 expression with RNA interference (RNAi) and then observed the inhibitory effects on the invasion and migration of human retinal microvascular endothelial cells (HRMECs). Methods: Small interfering RNAs against MMP-2 mRNA and MMP-9 mRNA were synthesized.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Most of such studies focused on cancer cells in which silencing of selected MMP expression resulted in the inhibition of the cell migration and invasion to other tissues (Sun et al, 2008;Tsung et al, 2008;Shen et al, 2012;Tang et al, 2013;Li et al, 2014). Also in other cell types, such as human retinal microvascular endothelial cells (HRMECs), decrease of MMPs expression, for example, MMP-2 and MMP-9, resulted in the inhibition of cell invasion and migration (Gu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Most of such studies focused on cancer cells in which silencing of selected MMP expression resulted in the inhibition of the cell migration and invasion to other tissues (Sun et al, 2008;Tsung et al, 2008;Shen et al, 2012;Tang et al, 2013;Li et al, 2014). Also in other cell types, such as human retinal microvascular endothelial cells (HRMECs), decrease of MMPs expression, for example, MMP-2 and MMP-9, resulted in the inhibition of cell invasion and migration (Gu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The best-described proteins related to these processes are metalloproteinases 2 and 9 (MMP-2 and MMP-9). These proteins have acidic properties, are rich in cysteine, and promote angiogenesis as they act to degrade the extracellular matrix, increasing the filtering of molecules that modify the microenvironment finally promoting the formation of new blood vessels [ 11 ] ( Figure 2(b) ).…”
Section: Molecular Mechanismsmentioning
confidence: 99%
“…MMP-2 can degrade components such as type IV collagen, fibronectin, elastin and denatured interstitial collagen (15). Mason found that MMP-2 can promote the migration of SMC, inhibit the invasion and migration of human retinal microvascular endothelial cells, and change vascular remodeling (16,17). MMP-2, which is localized in cardiomyocytes, can degrade type-IV collagen and other bioactive molecules, and is overexpressed in head and neck squamous cell carcinomas during cancer invasion and metastasis (18).…”
Section: Discussionmentioning
confidence: 99%
“…MMP-2, which is localized in cardiomyocytes, can degrade type-IV collagen and other bioactive molecules, and is overexpressed in head and neck squamous cell carcinomas during cancer invasion and metastasis (18). A survey of available literature shows that MMP-2 expression was suppressed with RNA interference (RNAi), and its inhibitory effects were observed on the invasion and migration of human retinal microvascular endothelial cells (19). MMP-2 upregulation has been implicated in the pathophysiology of atherosclerosis (20).…”
Section: Discussionmentioning
confidence: 99%